Perancangan dan Pembuatan Media Interaktif Fisika Suhu dan Kalor Bagi Anak SMP kelas VII Berbasis Android - Tjio Roy Abrianto Suciono; Gregorius Satia Budhi; Silvia Rostianingsih (Jurnal Infra, 2016)
At this modern age, interactive media program is already widely used for learning. Making the interactive media program aims to make students learn more class VII although not in school hours. This is done so that the students of class VII, can make a more effective and less confused in school learning at the temperature and heat chapter. The program used is Unity using the programming language C sharp.In the interactive media program there are 5 material ie shops, schools, parks schools, offices, and homes. Every material has a different learning but still in the learning of temperature and heat. Exam contained in the interactive media program includes a wide thermometer, temperature formula, formula substances expansion, expansion events, and heat transfer. The material has been taken through the stages of an interview with a teacher of Physics.Based on the results of the questionnaire, 55% expressed the view on a good program, 75% said that the storyline in targeted programs, 76.25% stated that the program is easy to play, 80% stated that the program is easy to understand, and 85% stating that the program as a whole can help understanding the physics lesson.